A Case of Digital Superficial Angiomyxoma - Gang LI; Liansheng ZHONG (Chinese Journal of Plastic and Reconstructive Surgery, 2020)
ABSTRACT: Superficial angiomyxoma (SA) is a rare superficial benign tumor of the skin that is characterized by slow growth. It is painless, non-invasive, and prone to relapse. It commonly occurs on the head, neck, trunk, and limbs and in the genital region. Herein, we describe a case of a 33-year-old man who presented with a soft tender tumor measuring 1.5 × 2.0 cm on the lateral aspect of the left second finger. The histopathology of the tumor indicated that it was a lobulated tumor rich in myxoid stroma and parenchymal blood vessels in the dermis, with spindle-to-stellate tumor cells in higher-power view and no mitotic or atypical figures. Immunohistochemical studies revealed that the tumor cells were positive for CD34 and negative for S100. Based on these clinical and histological findings, the patient was diagnosed with SA.